MAIN PARTICULARITY OF THE STRATEGIC DEVELOPMENT ENTERPRISE SMALL BUSINESS IN HOUSING CONSTRUCTION - I. C. Gadzhiev (Вестник Дагестанского государственного технического университета: Технические науки)
The main particularities and possibility of the strategic development small building enterprise are considered in sloppy condition modern market. The methods of the shaping tense plan operation and developments enterprise small business is offered.